Hemangiosarcoma hepático con metástasis a útero en un felino. Reporte de un caso - Ochoa Amaya, Julieta E.; Roque Rodríguez, Anita; Rodríguez Jiménez, Willinton (Revista Colombiana de Ciencias Pecuarias, 2009)
Summary The Haemangiosarcoma (HSA) is a malignant tumor of the vascular endothelium. It is a rare neoplasic in cats, just a 2% are reported from all the malignant tumors presented this species and is highly metastasic. The hepatic HSA embraces from 0 to 6-12% of the primary hepatic neoplasics. In this report a case of a feline patient which was suffering from one month of evolution abdominal dilatation, and tree day abdominal pain and anorexia is presented. During necropsy hydrothorax, right cardiac dilatation, liver with white or light yellow mottled appearance on cut surfaces of 1-2 mm of diameter and necrotic multifocal zones with dark red color and in the uterus, dilatation of the left horn with multiples solid masses with bloody content were found. The case was microscopically diagnosed as a hepatic HSA with metastasis to the uterus.